Cultures of curriculum - Joseph, Pamela Bolotin (Studies in curriculum theory, 2011)
"Using "cultures of curriculum" as a lens, this clear, compelling text reveals and critically examines the belief systems and classroom practices of curricular orientations in contemporary American society. It is designed to foster awareness, examination, and deliberation about the curricula planned for and carried out in classrooms and schools; to inspire conversations about theory and practice as well as political, social, and moral issues; and to expand critical consciousness about approaches to curriculum and practice. Readers are encouraged to give serious attention to the issues this book raises for them, and to join with their colleagues, students, and communities in considering how to create curricula with purpose and congruent practices and to reculture classrooms and schools. A framework of inquiry is presented to facilitate such reflection and to accomplish these goals."--Publisher's description.